Influencia de la epigenética sobre la expresión del gen IL-1B en pacientes con diabetes mellitus tipo 2 - Bergonzi, María Fernanda (2018)
Diabetes Mellitus type 2 (DM2) begins when two factors co-exist: insulin resistance (IR) and deficient insulin secretion by the ? cells. In DM2, a state of systemic subclinical inflammation secondary to the hyperactivity of innate immunity is observed. The state of subclinical inflammation has a direct implication in the development of the IR and in the progressive failure of the pancreatic ? cell. Subclinical inflammation depends on the circulating levels of inflammatory molecules, including Interleukin 1 beta (IL-1?), which is the prototype of a pro-inflammatory molecule and considered one of the main cytokines, since it actively participates in the pathophysiological processes of those metabolic alteration. The objectives of this work were: to study the levels of circulating IL-1 ? and the expression of mRNA IL-1 ? in peripheral blood mononuclear leukocytes, to evaluate their correlation with methylation patterns and the rs16944 polymorphism (-511C / T ) of the gene promoter. To this end, a group of 30 patients with a recent diagnosis of metabolically decompensated DM2 were studied at baseline and after 6 and 12 months of treatment to achieve compensation.\nAt each stage of the patients' study, the biochemical-clinical variables, the mRNA and protein expression, the promoter methylation patterns and the rs16944 polymorphism variants were evaluated. The study of mRNA expression and protein expression was performed by one-way ANOVA for paired samples and Bonferroni post-hoc test. Statistical analysis of pre and post-intervention mRNA expression was performed through linear regression, with age and sex as covariables. The genotypic frequencies were calculated by direct counting and evaluated if the SNPs were in Hardy Weinberg equilibrium through the Chi square test.\nAfter treatment, individuals achieved a clear decrease in fasting blood glucose and glycosylated hemoglobin, but no significant changes were found in IL-1? mRNA expression or levels of circulating IL-1?. In all cases, the individuals that showed the greatest decreases in glycemia and HbA1c were those that showed a greater increase in the level of circulating IL-1? (p = 0.040). The expression of IL-1? mRNA was not significantly affected by any of the biochemical and clinical variables analyzed in this work.\nIn the analyzed region of the promoter of the IL-1? gene, 3 CpG sites were found that significantly decreased their methylation percentage after treatment. Furthermore, the percentage of methylation at these sites was negatively correlated with the protein expression level of IL-1? (p = 0.016, r = -0.519, p = 0.022, r = -0.498, and p = 0.048, r = -0.400 , respectively).\nAt the beginning of the treatment, a significant association was found between the presence of the polymorphic T allele of rs16944 in the IL-1? gene and the lower expression of IL-1? mRNA (p = 0.006). The highest glycemic values were associated with high levels of circulating IL-1? protein (p = 0.015). The homozygous TT genotype was associated with better metabolic control, demonstrated by a greater decrease in fasting blood glucose after 6 (p = 0.002, r = -0.631) and 12 (p = 0.007, r = -0.734) months of treatment.\nThese results contribute to knowledge of the complex physiopathology of DM2.